The prospects of development of the citrus production in the Neretva valley in the context of contemporary tendencies : Perspektive razvoja hrvatskog agrumarstva u dolini Neretve u kontekstu suvremenih tendencija - Paladin, Ivana (Array, 2020)
In most countries of the world where citrus fruits are grown, including Croatia, several viruses and virus-like agents exist limiting the production and sale of citrus fruits. The most common among them is Citrus tristeza virus (CTV) which causes a decrease in tree fertility and lushness. The aim of this paper is to illustrate the large scale of consequences caused by the CTV in Spain during the 20th century. More than 44 million citrus trees grafted on sour orange (Citrus aurantim L) rootstock sourhad decayed over a period of 10 years due to the intensing spread of CTV. The approaches that addressed the problem of infection of large citrus growing areas in Spain will be presented. Based on the experience in Spain, this paper will show the possibilities of implementing systematic expert measures which would eradicate or minimize the presence of CTV in the area of the Neretva valley, the most important citrus growing area in Croatia. A large number of researches have been carried out on the presence and the outspread of CTV in the Neretva Valley from 2005 to 2019. During this period, the highest percentage of virus outspread was observed in 2006, when CTV was detected in 80% of the collected samples. The virus was regularly detected in the Neretva valley in all the years the research was conducted. The problem of CTV has been present for many years and the pathogen is still spreading, which indicates the need to take some measures to prevent this continuous spreading. Among the most important and effective measures is the control of viral diseases in the propagation materials and the mother blocks and planting virus-free plants in accordance with the provisions of the Ordinance on placing reproductive planting material and seedlings intended for fruit production on the market (OG 9/17, 39/20), which contain European Union Directives 2008/90 / EC, 2014/96 / EU, and 2014/98 / EU.